In-cell discontinuous reconstruction path-conservative methods for non conservative hyperbolic systems - Second-order extension - Pimentel García, Ernesto; Castro-Díaz, Manuel Jesús; Chalons, Christophe; Morales-de-Luna, Tomás; Parés-Madroñal, Carlos María (Elsevier, 2022)
We are interested in the numerical approximation of discontinuous solutions in non conservative hyperbolic systems. An extension to second-order of a new strategy based on in-cell discontinuous reconstructions to deal with this challenging topic is presented. This extension is based on the combination of the first-order in-cell reconstruction with the standard MUSCL-Hancock reconstruction. The first-order strategy allowed in particular to capture exactly the isolated shocks and this new second-order extension keep this property. Moreover, the well-balanced property of the method is also studied. Several numerical tests are proposed to validate the methods for the Coupled-Burgers system, Gas dynamics equations in Lagrangian coordinates and the modified shallow water system.
Keywords: Método de los volúmenes finitos; In-cell reconstruction; Path-conservative methods; Shock-capturing methods; Finite volume methods; MUSCL-Hancock; Nonconservative hyperbolic systems